Does access to finance condition firms’ green investment responses to environmental pressure? Evidence from Vietnam - Dinh Duc Truong (PLoS ONE, 2026)
Environmental regulation is widely viewed as a key driver of firms’ green investment, yet evidence remains mixed, particularly in emerging economies where financial constraints are pervasive. This study examines whether environmental pressure is associated with firms’ green investment and whether this relationship is conditioned by financial constraints. Using firm-level data from the World Bank Enterprise Survey in Vietnam, we estimate nonlinear probability models with interaction terms, controlling for firm characteristics as well as industry and regional fixed effects. The results show that environmental pressure is positively associated with green investment, but the magnitude is modest. Financial constraints significantly reduce the likelihood of green investment and weaken firms’ responses to environmental pressure. Marginal effects indicate that regulatory pressure is more likely to translate into investment among firms facing lower financial constraints, while the association becomes negligible for financially constrained firms. These findings highlight a conditional mechanism through which environmental regulation operates. Regulatory pressure alone is insufficient to induce widespread green investment when financial constraints are binding. Instead, its effectiveness depends critically on firms’ financial conditions. By providing firm-level evidence from an emerging economy, this study contributes to a more integrated understanding of how regulatory and financial factors jointly shape environmental investment behavior.